ANALYSIS OF THE EFFECT OF VARIATION OF ELECTRIC CURRENT AND HOLDING TIME ON THE TEMPERING PROCESS TO IMPROVE MECHANICAL PROPERTIES OF AUTOMATIC TRANSMISSION SPREAD SHAFTS OF SUPRA X150 MOTORCYCLE - Sansosa, Aa; wahyudin, anggi (Jurnal Mekanika dan Manufaktur, 2023)
ABSTRACTA study has been carried out on the transmission shaft or main shaft used on the Supra x150 motorcycle vehicle. The material used for the main shaft component is made of SCr420 steel, which is an alloy steel similar to SAE 4118 or JIS SCM 420. The research carried out is the Temper Process with the aim of reducing hardness but increasing other mechanical properties, namely the more ductile nature of the material by how to vary the tempering temperature with the electric current used. This tempering process uses an induction furnace. The electric current used starts from 79 A, ​​80 A and 81 A with a holding time of 15 s, 20 s and 25 s for each Ampere.Tempering process with the required temperature and time is very influential on the hardness of the material. The lower the temperature and the shorter the Tempering process time, the higher the hardness of the material, and vice versa, the higher the temperature and the longer the Tempering process, the lower the hardness of the material.From the results of the tests that have been carried out, it is obtained that some cannot be applied, but if seen from the electric current used, the efficient one is test number 4 because it uses a current of 79 Amperes Keywords: Tempering, Current Strength, Supra X150 Motor, SAE 4118 Steel